2021
DOI: 10.3389/fsoc.2021.742287
|View full text |Cite
|
Sign up to set email alerts
|

Womens’ Career Progression in an Australian Regional University

Abstract: This article examines the link between terms of employment (full time, part time and casual) at an Australian regional university and women’s career progression. The literature identifies lack of transparency in recruitment, promotion and retention; mobility and location; and management perceptions of women’s choice to work flexibly as factors impacting on career progression. However, the voices of women working in regional universities and particularly those of professional staff are often not present in curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Unfortunately, women's education and employment opportunities are sometimes not as great as those for men (Sarwar & Imran, 2019). Various barriers influence women's career advancement in higher education (White & Goriss-Hunter, 2021). A survey of three hundred students showed that parents' economic status, social class, and financial support influenced students' career decisions at their educational level (Sahu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, women's education and employment opportunities are sometimes not as great as those for men (Sarwar & Imran, 2019). Various barriers influence women's career advancement in higher education (White & Goriss-Hunter, 2021). A survey of three hundred students showed that parents' economic status, social class, and financial support influenced students' career decisions at their educational level (Sahu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%